THE EFFECT OF MOTIVATION, WORK DISCIPLINE AND WORK ENVIRONMENT ON EMPLOYEE WORK PRODUCTIVITY AT PDAM GIRI TIRTA GRESIK - Khoirul Anam; Is Fadhilah (Suluh Adiluhung Publisher (SAPub), 2025)
This study aims to determine the effect of motivation, work discipline and work environment on work productivity at PDAM Giri Tirta Gresik. The population in this study were all employees at PDAM Giri Tirta Gresik totaling 318 employees. The sampling technique in this study was non-probability with accidental sampling. The sample was obtained using the slovin formula. The sample in this study amounted to 72 respondents. Data collection techniques were observation, questionnaires, literature studies and interviews. The data analysis method used in this study was Multiple Linear Regression This study aims to determine the effect of motivation, work discipline and work.